The 2nd Polish Scientific Conference “Man- Information. Book. Cyberculture”. Toruń, 9–10 March 2017 - Balcerek, Mariusz (Folia Toruniensia, 2017)
On 9–10 March 2017 in Collegium Humanisticum of Nicolaus Copernicus University in Torun there took place the Second Polish Scientific Conference titled “Man – Information. Book. Cyberculture”. It was organized by the Scientific Circle of Students and PhD Students ePRINT, which operates in the Institute of Scientific Information and Bibliology of Nicolaus Copernicus University. It is the third conference organized by young academics from Toruń. The participants of the conference had an opportunity to listen to a dozen of interesting speeches, the authors of which discussed new methods of transmitting knowledge along with possibilities and problems which may be encountered by users of the Internet.